2014
DOI: 10.1152/ajprenal.00094.2014
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II stimulates fibronectin protein synthesis via a Gβγ/arachidonic acid-dependent pathway

Abstract: Alexander LD, Ding Y, Alagarsamy S, Cui X. Angiotensin II stimulates fibronectin protein synthesis via a G␤␥/arachidonic aciddependent pathway. Am J Physiol Renal Physiol 307: F287-F302, 2014. First published June 11, 2014 doi:10.1152/ajprenal.00094.2014.-In rabbit proximal tubular cells, ANG II type 2-receptor (AT 2 )-induced arachidonic acid release is PLA 2 coupled and dependent of G protein ␤␥ (G␤␥) subunits. Moreover, ANG II activates ERK1/2 and transactivates EGFR via a c-Src-dependent mechanism. Arachi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 53 publications
(61 reference statements)
0
6
0
Order By: Relevance
“…These results show that STAT3 is involved in stretch-induced fibronectin and TGF-␤1 expression and that stretch-stimulated fibronectin expression in HK-2 cells was mediated by TGF-␤1. (11,24,50) and fibronectin (2,59,60). Moreover, previous studies from this laboratory have shown that mechanical stretch activates c-Src in renal tubular cells (1).…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…These results show that STAT3 is involved in stretch-induced fibronectin and TGF-␤1 expression and that stretch-stimulated fibronectin expression in HK-2 cells was mediated by TGF-␤1. (11,24,50) and fibronectin (2,59,60). Moreover, previous studies from this laboratory have shown that mechanical stretch activates c-Src in renal tubular cells (1).…”
Section: Resultsmentioning
confidence: 90%
“…Western blot analysis was carried out as previously described (1,2). Briefly, proteins were extracted with buffer containing 50 mM Tris, pH 7.2, 1% (vol/vol) Triton X-100, 1 mM Na 3VO4, 1 mM EGTA, 0.2 mM phenylmethanesulfonyl fluoride, 25 g/ml leupeptin, and 10 g/ml aprotinin.…”
Section: Methodsmentioning
confidence: 99%
“…1 A ). It should be noted that these molecules were able to induce cellular signaling as witnessed by the activation of ERK1/2 (21). However, based on previous reports on the transactivation of EGFR, we cannot exclude that other arachidonic acid derivatives are able to induce CSF‐1R phosphorylation (22).…”
Section: Resultsmentioning
confidence: 99%
“…Fn1 expression, also an extracellular matrix glycoprotein related to tissue repair and cell adhesion/migration (Ren et al, 2013), was found to be significantly increased after PD in normal and diabetic mice, suggesting that its production is mediated by renin release. Recent studies have already shown that AngII stimulates Fn synthesis in proximal tubular (Alexander et al, 2014) and collecting duct cells (Cuevas et al, 2015) by different pathway. An important point is that wound healing process occurs in three phases: inflammation, proliferation, and remodeling.…”
Section: Discussionmentioning
confidence: 99%